Cognitive and metacognitive reading strategies of Iranian EFL learners / Reza Aghaei - Aghaei, Reza (2011)
This study explored the cognitive and metacognitive reading strategies employed by Iranian EFL learners. It also examined significant relationships between cognitive and metacognitive reading strategies and the gender and English proficiency of the learners. Further, it looked at the impact of explicit teaching of these strategies on reading performance and self-efficacy. The study employed two instruments for data collection: a questionnaire adopted from Chamot and O’Malley’s (1994) cognitive and metacognitive strategies and think-aloud protocols. A total of 300 high school students participated in this study. The study, mixed method in design, utilized quantitative and qualitative methods. Independent t-tests and analysis of think-aloud protocols showed that cognitive reading strategies were used more frequently than metacognitive ones. Further, high-proficient students used metacognitive reading strategies more frequently than low-proficient students. However, no gender differences were found with respect to the use of cognitive and metacognitive reading strategies based on the results of the independent t-tests and think-aloud analysis. 1T Analysis of the transcripts of the think-aloud protocols suggests1T that the difference between high-proficient students and low-proficient students is not only the frequency of strategies used but also their quality 1Tand the way they use them. Analysis of the transcripts does not indicate1T differences between male and female students regarding frequency of strategies, though there are differences with respect to the quality and the way they used strategies. The findings of this study indicate that Iranian certain context of leaning strategy that is, teachers' instructional goals and assessment formats use determine learners’ strategy use. To test the impact of explicit teaching of cognitive and metacognitive reading strategies on reading performance and self-efficacy, the study examined a control group and an experimental group. The experimental group achieved significantly better results than the control group. Results of paired-sample t-tests and independent t-tests and effect size showed that reading comprehension, strategy and self-efficacy can be improved with strategy instruction; that within certain contexts, strategy instruction contributes to independent reading behaviours. Additional analysis showed that the experimental group developed a positive attitude after strategy instruction and was able to transfer the strategies to other languages and reading materials. In sum, teaching reading strategies promoted learners’ autonomy as students become aware that strategy allows them to learn independently of teachers. The results suggest that language practitioners should teach strategies to EFL learners and encourage their use in the language learning process to promote learning and learners' autonomy.